Cellulose Microfibrils as a Pore Former in Electroless Co-Deposited Anodes for Solid Oxide Fuel Cells. (30th May 2017) - Turnbull, Rob James; Shearer, Neil; Wilson, Callum
Abstract : A study was conducted to investigate the feasibility of Cellulose Microfibrils (CMF) as a pore former in the manufacture of Solid Oxide Fuel Cell (SOFC) anodes using Electroless Co-Deposition (ECD). Previous work into the use of ECD to produce SOFC anodes has found that the lack of porosity has restricted the maximum power density of the cell. Cellulose Microfibrils' unique combination of properties and morphologies should produce the required microstructure for SOFC's electrodes. Cellulose Microfibrils were evaluated as a pore former by their inclusion (using various bath loadings) in the production of ECD anodes. The anodes produced were then evaluated using a Scanning Electron Microscope, Mercury Porosimetry and Electrochemical Impedance Spectroscopy. The results showed that an anode produced with a 10 g/l of a 1% solution of CMF as pore former, improved the open circuit voltage, maximum power density by reducing the overall resistance of the cell.